2016
DOI: 10.1016/j.jlumin.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Excited-state proton transfer of 4-hydroxyl-1, 8-naphthalimide derivatives: A combined experimental and theoretical investigation

Abstract: The photophysical properties of N-butyl-4-hydroxyl-1, 8-naphthalimide (BOH) and N-(morpholinoethyl)-4-hydroxy-1, 8-naphthalimide (MOH) in various solvents are presented and the density functional theory (DFT) / time-dependent density functional theory (TDDFT) methods at the B3LYP/TZVP theoretical level are adopted to investigate the UV-visible absorption and emission data. An efficient intermolecular excited-state proton transfer (ESPT) reaction occurs for both compounds in DMSO, methanol and water. In aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…For example, when new ESPT chromophores are developed, the design strategies and possible mechanisms are proposed based on the experimental results. However, the suggested mechanism is usually not completely corrected and sometimes problematic, thereby requiring further theoretical studies to validate or invalidate; this can provide guidance for developing new ESPT chromophores . When multiple protons are involved, such as in excited-state double PT (ESDPT), whether the mechanism is stepwise or concerted is usually under debate among experimental scientists; , extensive theoretical studies are necessary to resolve this controversy. When solvent molecules participate in ESPT as proton acceptor or catalyst, the size of the solute·(solvent) n cluster is difficult to determine experimentally, and theoretical studies are necessary. …”
Section: Introductionmentioning
confidence: 99%
“…For example, when new ESPT chromophores are developed, the design strategies and possible mechanisms are proposed based on the experimental results. However, the suggested mechanism is usually not completely corrected and sometimes problematic, thereby requiring further theoretical studies to validate or invalidate; this can provide guidance for developing new ESPT chromophores . When multiple protons are involved, such as in excited-state double PT (ESDPT), whether the mechanism is stepwise or concerted is usually under debate among experimental scientists; , extensive theoretical studies are necessary to resolve this controversy. When solvent molecules participate in ESPT as proton acceptor or catalyst, the size of the solute·(solvent) n cluster is difficult to determine experimentally, and theoretical studies are necessary. …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] However, examples of a clear identication of the CIP* spectral signatures are scarce. [23][24][25][26][27][28] Few studies reported an intermediate uorescence between the ROH* and RO À * bands that was attributed to the contact ion pairs but this was observed only in supercritical, 23 frozen or strongly acidic aqueous solutions 24,25 and aprotic organic solvents. 26,27 Therefore, it remains unclear whether the CIP* emission would be detectable in protic solvents at a moderate pH range.…”
Section: Introductionmentioning
confidence: 99%
“…Taken as a whole, the present results provide a coherent theoretical description of the photodissociation of the 7-hydroxyflavylium cation, promoted by a significant shift of charge away from the OH group in the first singlet excited state, leading smoothly to the excited conjugate base and a protonated water cluster. The consistency of the results of the present study can be attributed to a combination of several factors: (1) our theoretical approach (TD-DFT with the B3-LYP functional and def2-TZVP basis set utilizing Grimme's D3 dispersion correction), which was found to give results similar to high-level ab initio methods for anthocyanins (25); (2) the modeling of the solvent effect by immersing the photoacid, hydrogen-bonded to a cluster of discrete water molecules (12)(13)(14)(15)(16)(17)(18)(19), into a water-like continuum solvent (COSMO); (3) the fact that the S 1 state of the flavylium cation (and of anthocyanins in general) (33) is dominated by HOMO-LUMO contributions and is well separated in energy from S 2 and higher excited states; and (4) unlike a neutral or anionic photoacid, the proton is transferred from the excited cationic photoacid to water to form a neutral excited conjugate base, avoiding Coulombic interactions between the proton and the conjugate base. As such, the present approach should serve as a useful framework for the theoretical treatment of intermolecular ESPT in other molecular systems.…”
Section: Resultsmentioning
confidence: 90%
“…1), agree quite well with the corresponding experimental values (3) of 2.90 eV (427 nm) and 2.61 eV (475 nm) for these two species. As shown by a number of recent studies, proper theoretical treatment of intermolecular ESPT requires the use of a discrete proton acceptor such as a solvent cluster (12)(13)(14)(15)(16)(17)(18)(19). Indeed, upon hydrogen-bonding AH + to a discrete water molecule or to clusters of three or five discrete water molecules (optimized in a COSMO aqueous environment), the S 1 energy decreased by about 0.07-0.08 eV (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation